Retrospective analysis of the risk of neoplasia associated with unilateral maxillary sinus opacification on computed tomography. Issue 12 (7th December 2022) - Mughal, Z; Daffu, K; Adeoti, R; Swaminathan, R; Henney, S
Abstract: Background: Unilateral maxillary sinus opacification on computed tomography may reflect an inflammatory or neoplastic process. The neoplasia risk is not clear in the literature. Methods: In this retrospective study, computed tomography sinus scans performed over 12 months were screened for unilateral maxillary sinus opacification, and the rates of inflammatory and neoplastic diagnoses were calculated. Results: Of 641 computed tomography sinus scans, the rate of unilateral maxillary sinus opacification was 9 per cent. Fifty-two cases were analysed. The risk of neoplasia was 2 per cent (inverted papilloma, n = 1). No cases of unilateral maxillary sinus opacification represented malignancy, but one case of lymphoma had an incidental finding of unilateral maxillary sinus opacification on the contralateral side. Patients with an antrochoanal polyp ( n = 3), fungal disease ( n = 1), inverted papilloma and lymphoma all had a unilateral nasal mass. Conclusion: Our neoplasia rate of 2 per cent was lower than previously reported. A unilateral mass was predictive of pathology that required operative management. Clinical findings, rather than simple findings of opacification on computed tomography, should drive the decision to perform biopsy.